KONDISI SOSIAL EKONOMI NELAYAN SUKU BAJOE DI DESA WAIWURING KECAMATAN WITIHAMA KABUPATEN FLORES TIMUR - K. L. Saburi, Patrisia Yuliana; Rahmawati, Arfita; Sunimbar, Sunimbar (Jurnal Geografi, 2022)
This research aims to (1) Know the socio-economic conditions of Bajoe fishermen in Waiwuring Village (2) Know the empowerment program of fishermen in obtaining business capital to improve the welfare of Bajoe fishermen in Waiwuring Village (3) Know the spatial patterns of bajoe fishing communities in Waiwuring Village. This type of research is descriptive research, which is a type of research that has the aim to explain specifically a symptom, event, that occurs at the present moment or actual problems by using data in the form of quantitative data and qualitative data. The population in the study was as many as 100 heads of families. The sample size in this study was 50 heads of families. The data source consists of primary data and secondary data. Data collection techniques are: questionnaires, interviews, observations and documentation. The data analysis techniques used are qualitative analysis and quantitative analysis. The analsisis technique of spatial patterns uses interpolation techniques. Research results: (1) socio-economic conditions of the Bajoe fishing community when viewed from net income, health, education and housing are still classified in poor or less decent communities (not yet prosperous),, (2) bajoe fishing communities still rely on their own financial capital., (3) the spatial pattern of the fishing community of the Bajoe Tribe forms a grouping pattern.